Mechanical effects of negative pressure wound therapy on abdominal wounds – effects of different pressures and wound fillers. Issue 1 (23rd November 2017) - Torbrand, Christian; Anesäter, Erik; Borgquist, Ola; Malmsjö, Malin
Abstract: The mechanical deformation of the wound edge resulting from negative pressure wound therapy (NPWT) at the standard setting of around −120 mmHg has positive effects in promoting wound healing. However, it may cause pain to the patient during treatment. It is therefore important to study the mechanical effects of the wound edges using lower pressure and different wound fillers. Abdominal wounds were created on eight pigs. The wounds were sealed for NPWT using foam or gauze. Negative pressures between −20 and −160 mmHg were applied, and the decrease in wound diameter and the force with which the edges of the wound were drawn together (wound edge force) were measured. Increasing levels of negative pressure resulted in a gradual decrease in wound diameter and increase in wound edge force and reached a maximum at −120 mmHg, which is the pressure commonly used in clinical practice. Both the decrease in wound diameter and the increase in wound edge force was greater with foam than with gauze. A pressure of −80 mmHg has only 15% less effect than −120 mmHg, while a lower pressure (−40 mmHg) diminished the effects on diameter and force markedly. The NPWT‐induced decrease in wound diameter and increase in wound edge force are greater at higher levels of negative pressure and when using foam than when using gauze as a wound filler. It may be possible to tailor the type of wound filler and level of negative pressure to obtain the best balance between wound healing and patient comfort.